PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS GAME UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV DI SD NEGERI 023 KUNTO DARUSSALAM - Wahyu Ningtias; Rejeki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of game-based learning media, Wordwall, in mathematics education has a positive impact on improving student learning outcomes. The purpose of this research is to analyze the constraints and impacts encountered in the use of game- based learning media to enhance the mathematics learning outcomes of fourth- grade students at SD Negeri 023 Kunto Darussalam. The subjects of the study consisted of 28 fourth-grade students at SD Negeri 023 Kunto Darussalam. This research utilized the Classroom Action Research (CAR) method, collected through observation, documentation, tests of student learning outcomes, and interviews. The results showed that with the conventional method, only 25% of students achieved minimum competency standards (KKM), whereas after the use of the Wordwall game-based learning media, student learning outcomes improved by 92.86%, with very good criteria in the assessments by teachers and students. Based on these results, it can be concluded that the advancement of technology in the education sector improves students' ability to understand and master mathematics independently or collaboratively.